1990
DOI: 10.1136/thx.45.11.846
|View full text |Cite
|
Sign up to set email alerts
|

Management of post-tuberculous complex aspergilloma of the lung: role of surgical resection.

Abstract: Of 14 patients with complex aspergilloma complicating healed tuberculosis, 12 underwent lobectomy or pneumonectomy for recurrent haemoptysis. No deaths occurred, though one patient needed re-exploration for bleeding. There was no postoperative worsening of dyspnoea despite a mean forced vital capacity (FVC) of 60% predicted for the patients undergoing surgery and of 20% predicted for two patients with severe restrictive defects, perhaps owing to the fact that there was little or no function in the resected par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Even in this case, however, surgical therapy is considered elective for aspergilloma, or aimed at preventing its complications (especially when hemoptysis is present) [12], but experience with invasive aspergillosis is still limited [13]. For inoperable patients in whom the problem becomes bleeding, this can be controlled by embolization of the bronchial arteries [14].…”
Section: Discussionmentioning
confidence: 99%
“…Even in this case, however, surgical therapy is considered elective for aspergilloma, or aimed at preventing its complications (especially when hemoptysis is present) [12], but experience with invasive aspergillosis is still limited [13]. For inoperable patients in whom the problem becomes bleeding, this can be controlled by embolization of the bronchial arteries [14].…”
Section: Discussionmentioning
confidence: 99%
“…Provided that patients are carefully selected (simple aspergilloma, single lesion without sequelae), such as our case 5, surgical resection offers the best chance of cure, with low mortality and morbidity. [6][7][8][9][10] However, in complex aspergilloma (with pleural or parenchymal sequelae) such as that afflicting our cases 1, 3, and 4, the prognosis is not always evaluable. Case 2 was a patient with a residual cavity complicated with aspergilloma after Klebsiella pneumonia.…”
Section: Discussionmentioning
confidence: 88%
“…Neovascularization and broncho-pulmonary shunt formation, could be one reason for bleeding complications during surgery of aspergilloma complex, bronchiectasis [21,22] and infrequently lung carcinoma. During this study, we observed that the mean value of measured activated partial thromboplastine time during the course of surgery 49.47 s (SD^8.39), was significantly high ðP ¼ 0:003Þ when compared to pre-operative measurement of 37.01 s (SD^6.38) in 10 of the patients who developed bleeding complications.…”
Section: Discussionmentioning
confidence: 99%